Sorting algorithms for single‐particle imaging experiments at X‐ray free‐electron lasers. (22nd October 2015) - Bobkov, S. A.; Teslyuk, A. B.; Kurta, R. P.; Gorobtsov, O. Yu.; Yefanov, O. M.; Ilyin, V. A.; Senin, R. A.; Vartanyants, I. A.
Abstract : Modern X‐ray free‐electron lasers (XFELs) operating at high repetition rates produce a tremendous amount of data. It is a great challenge to classify this information and reduce the initial data set to a manageable size for further analysis. Here an approach for classification of diffraction patterns measured in prototypical diffract‐and‐destroy single‐particle imaging experiments at XFELs is presented. It is proposed that the data are classified on the basis of a set of parameters that take into account the underlying diffraction physics and specific relations between the real‐space structure of a particle and its reciprocal‐space intensity distribution. The approach is demonstrated by applying principal component analysis and support vector machine algorithms to the simulated and measured X‐ray data sets.